FUTURE CAREER PATHS: EXPLORING HEALTH AND TECHNOLOGY STUDY PROGRAMMES FOR GENERATION Z: JEJAK KARIER MASA DEPAN: EKSPLORASI PROGRAM STUDI KESEHATAN DAN TEKNOLOGI BAGI GENERASI Z - Krisnita Dwi Jayanti; Arshy Prodyanatasari; Eggy Dio Otista (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
The low Gross Enrollment Rate (GER) in higher education in Bojonegoro, particularly at SMA Negeri 1  Gondang, which is below 40 per cent, constitutes the primary urgency for implementing this community  service activity. This condition is exacerbated by students' limited information regarding study programs, future career prospects, and access to scholarships such as KIP Kuliah. This activity aimed to improve the  understanding and motivation of 12th-grade students in planning further studies, specifically in the field of  technology-based health. The method employed was participatory and interactive socialisation through interactive seminars and focus group discussions (FGD). The activity was conducted on January 28, 2026,  at the Hall of SMA Negeri 1 Gondang, Bojonegoro, with all 12th-grade students as the subjects. Data collection techniques utilised pre-tests and post-tests, observation sheets, and documentation, with instruments consisting of a ten-question multiple-choice questionnaire. Data analysis was performed using  descriptive quantitative analysis to measure the increase in understanding and descriptive qualitative  analysis to depict changes in student motivation. The results showed a significant increase in students'  understanding, evidenced by the rise in the average pre-test score from 42.86 to 93.88 on the post-test (a  119 per cent increase). Student enthusiasm was also evident from the numerous questions regarding study  programs at IIK Bhakta Kediri (midwifery, nursing, physiotherapy, medical laboratory technology, and  pharmacy), clinical practices, and graduate employment prospects. This activity concludes that  participatory socialisation effectively enhances students' understanding and motivation in planning further  studies. It is recommended that schools integrate study program exploration into sustainable career  guidance, provide technical assistance for scholarship applications, and expand the target to include 10th  and 11th-grade students.